Transformation of Au144(SCH2CH2Ph)60 to Au133(SPh‑tBu)52 Nanomolecules: Theoretical and Experimental Study - Nimmala, Praneeth Reddy; Theivendran, Shevanuja; Barcaro, Giovanni; Sementa, Luca; Kumara, Chanaka; Jupally, Vijay Reddy; Apra, Edoardo; Stener, Mauro; Fortunelli, Alessandro; Dass, Amala (The journal of physical chemistry letters, 2015)
Ultrastable gold nanomolecule Au144(SCH2CH2Ph)60 upon etching with excess tert-butylbenzenethiol undergoes a core-size conversion and compositional change to form an entirely new core of Au133(SPh-tBu)52. This conversion was studied using high-resolution electrospray mass spectrometry which shows that the core size conversion is initiated after 22 ligand exchanges, suggesting a relatively high stability of the Au144(SCH2CH2Ph)38(SPh-tBu)22 intermediate. The Au144 → Au133 core size conversion is surprisingly different from the Au144 → Au99 core conversion reported in the case of thiophenol, −SPh. Theoretical analysis and ab initio molecular dynamics simulations show that rigid p-tBu groups play a crucial role by reducing the cluster structural freedom, and protecting the cluster from adsorption of exogenous and reactive species, thus rationalizing the kinetic factors that stabilize the Au133 core size. This 144-atom to 133-atom nanomolecule’s compositional change is reflected in optical spectroscopy and electrochemistry.